Agricultural Implications of the Fukushima Nuclear Accident: The First Three Years - Nakanishi, Tomoko M.; Tanoi, Keitaro (Springer Nature, 2016)
Environmental Monitoring/Analysis; Agriculture; Plant Sciences; Ecology